SIALIC ACIDS AND AUTOIMMUNE DISEASE - Mahajan, Vinay S. (Immunol Rev, 2016)
An important underlying mechanism that contributes to autoimmunity is the loss of inhibitory signaling in the immune system. Sialic acid-recognizing Ig superfamily lectins or Siglecs are a family of cell surface proteins largely expressed in hematopoietic cells. The majority of Siglecs are inhibitory receptors expressed in immune cells that bind to sialic acid containing ligands and recruit SH2-domain containing tyrosine phosphatases to their cytoplasmic tails. They deliver inhibitory signals that can contribute to the constraining of immune cells and thus protect the host from autoimmunity. The inhibitory functions of CD22/Siglec-2 and Siglec-G and their contributions to tolerance and autoimmunity, primarily in the B lymphocyte context, are considered in some detail in this review. The relevance to autoimmunity and unregulated inflammation of modified sialic acids, enzymes that modify sialic acid, and other sialic acid binding proteins are also reviewed.